Fine-Grained Support of Security Services for Resource Constrained Internet of Things - Hyo Jin Ban; Jaeduck Choi; Namhi Kang (International Journal of Distributed Sensor Networks)
Internet of Things (IoT) technologies allow everyday objects to be capable of connecting to the Internet, thereby making smart and convenient daily life. Although users' daily lives can be convenient due to various smart services utilizing IoT, it can also be a target of attack through the Internet. Thus, security has now been recognized as mandatory technology to activate IoT based smart service. Several standard organizations related to IoT technologies recommend using the CoAP over DTLS protocol stacks for enabling secure communications between resource constrained things. In general DTLS, a cipher suite required to support specific security service should be negotiated between the CoAP client and server in the process of performing the DTLS handshake protocol. However, the handshake requires too much processing and transmission overhead in constrained IoT environment. To improve such an issue, this paper proposes a secure but efficient scheme for resource constrained things. The proposed scheme can selectively apply application data encryption or integrity to the DTLS record layer during an on-going secure session, thereby reducing the burden of DTLS handshake in resource constrained Internet of Things.